Designing Information Technology Architecture Based on TOGAF Methodology At Padang Karunia Group - Marwati, Arum (Jurnal Tata Kelola dan Kerangka Kerja Teknologi Informasi, 2022)
Padang Karunia Group (PKG) is engaged in four main business areas coal mining, coal trading, mining contractor and infrastructure and has consistently delivered coal product to domestic and overseas market. There are problems in the business processes of PKG’s everyday operations, such as: the waiting time for reports is over one day when it should be a few hours, data has more than one version and is not accurate, and demurrage (a charge payable to the owner of a chartered ship in respect of failure to load or discharge the ship within the time agreed). Issues occur because the role of IT is not optimal. The purpose of this study was to design an information technology (IT) architecture suitable for supporting the operation of the PKG. The correct IT architecture design can help companies to achieve their vision and mission. The right IT architecture for PKG will support all of its operations. The design of the IT architecture could be done with the existing framework using: EAP, TOGAF, FEA, DODAF, and Gartner Methodology. For this work the TOGAF was selected because it is open source, systematic, and thorough. Analysis was done using a business processes approach to obtain the IT needs mapped to the principles of business, information systems, applications, and information technology. The results from this study are a business architecture design, an information systems architecture, and a technology architecture appropriate to support the business of PKG.